Malaria Vectors Tend to Avoid the Indoor-Based Vector Control Tools in Wonji Sugar Estate, Oromia, Ethiopia - Kidane Lelisa; Lemu Golassa; Yitbarek Woldehawariat; Sisay Dugassa (SAGE Publishing, 2024)
Background: There is a paucity of data regarding resting habits and comparison of the physiological states of Anopheles mosquito populations from indoor and outdoor collection venues in Ethiopia. Therefore, this study aims to investigate resting behavior and age structure of the malaria vectors in Wonji Sugar Estate. Methods: Longitudinal entomological study was conducted at Wonji Sugar Estate from July 2018 to June 2020. Pyrethrum spray catches (PSC), Pit Shelter (PIT), and Oral Aspirators were used to collect adult Anopheles species from various resting sites. Mosquitoes were identified to the species using morphological keys. Finally, the resting behavior of Anopheles mosquitoes were determined using standard protocol. Results: A total of 1406 mosquitoes were collected from indoor and outdoor resting venues, with the outdoor resting population being significantly higher ( F  = 8.296, P  = .04). The number of half-gravid/gravid Anopheles species collected from outdoors was higher than that from indoor resting venues ( F  = 35.612, P  = .00). Eight two percent of the indoor sampled Anopheles species left the indoor venue before completing their gonotrophic cycle. Anopheles pharoensis and An. coustani cx. exhibited exophily rate of 83.4% and 100%, respectively. The overall parity rate of Anopheles gambiae s.l. was 45.7%. The highest parity rate, daily survival rate, and longevity of Anopheles gambiae s.l. was 66.7%, 0.874, and 7.399 days, respectively. Anopheles gambiae s.l. reached the infective stages for Plasmodium falciparum and P. vivax in February 2019. Conlusion: Anopheles mosquitoes, including the major malaria vector Anopheles gambiae s.l., showed predominantly exophilic habits, underscoring the need for outdoor vector control strategies in addition to indoor-based interventions. The increase in the nulliparous population indicates a higher risk of vector-human contact. Meanwhile, the extended lifespan of Anopheles gambiae s.l. observed during the dry season could increase the risk of infectious bites.